Application of Centri-voltammetry to Cytosensors: Cyto-centrivoltammetry. (1st September 2016) - Tepeli, Yudum; Barlas, Fırat Barış; Timur, Suna; Anik, Ulku
Abstract: In this work, a centri-voltammetric cytosensor suitable for the for detection of folate receptor positive cervical cancer (HeLa) cells was developed for the first time. In order to see the effect of centrifugation, developed cytosensor's performance was compared in terms of analytical characteristics values, in the presence and absence of centri-voltammetry. As a result, in the absence of centri-voltammetry, the linear range was found between 75 cells/mL and 10 6 cells/mL with limit of detection (LOD) value as 75 cells/mL and with R.S.D value of 3.5% (for 5.0 × 10 4 HeLa cells/mL (n = 3)). Meanwhile in the presence of centri-voltammetry, the linear range was found between 8.0 cells/mL and 5 × 10 6 cells/mL and LOD value was calculated as 8 cells/mL with R.S.D value of 4.7% for the same concentration.